A MECHANISTIC MODEL FOR INTERPRETATION OF HYDROGEN AND OXYGEN ISOTOPE RATIOS IN TREE-RING CELLULOSE - EVIDENCE AND IMPLICATIONS FOR THE USE OF ISOTOPIC SIGNALS TRANSDUCED BY PLANTS - Roden J.S.; Lin G.; Ehleringer J.R. (My University, 2000)
A mechanistic model is presented to quantify both the physical and biochemical fractionation events associated with hydrogen and oxygen isotope ratios in tree-ring cellulose. The model predicts the isotope ratios of tree-rings, incorporating both humidity and source water environmental information. Components of the model include (1) hydrogen and oxygen isotope effects associated with leaf water enrichment; (2) incorporation of leaf water isotope ratio values into photosynthetic carbohydrates along with the biochemical fractionation associated with autotrophic synthesis; (3) transport of exported carbohydrates (such as sucrose) from leaves to developing xylem in shoots and stems where cellulose is formed; (4) a partial exchange of oxygen and hydrogen isotopes in carbohydrates with xylem sap water during conversion into cellulose; and (5) a biochemical fractionation associated with cellulose synthesis. A modified version of the Craig-Gordon model for evaporative enrichment adequately described leaf water δD and δ18O values. The leaf water model was robust over a wide range of leaf waters for both controlled experiments and field studies, far exceeding the range of values to be expected under natural conditions. The isotopic composition of cellulose was modeled using heterotrophic and autotrophic fractionation factors from the literature as well as the experimentally derived proportions of H and O that undergo exchange with xylem water during cellulose synthesis in xylem cells of tree-rings. The fraction of H and O from carbohydrates that exchange with xylem sap water was estimated to be 0.36 and 0.42, respectively. The proportions were based on controlled, long-term greenhouse experiments and field studies where the variations in the δD and δ18O of tree-ring cellulose were measured under different source water isotopic compositions. The model prediction that tree-ring cellulose contains information on environmental water source and atmospheric vapor pressure deficit (related to relative humidity) was tested under both field and greenhouse conditions. This model was compared to existing models to explain cellulose isotope ratios under a wide range of source water and humidity conditions. Predictions from our model were consistent with observations, whereas other models showed large discrepancies as soon as the isotope ratios of source water and atmospheric water deviated from each other. Our model resolves the apparently conflicting and disparate interpretations of several previous cellulose stable isotope ratio studies.